Analysis of Factors that Lead to Financial Distress for Property and Real Estate Companies in Indonesia - Theresia Trisanti (Forum Inovasi Bisnis dan Manajemen, 2020)
This study is to examine and analyze the effect of the independent variables, namely profitability, liquidity, company size, leverage, and sales growth on the dependent variable in the form of financial distress. The population in this study was property and real estate companies listed on the Indonesia Stock Exchange for the period 2016 - 2019. By using purposive sampling technique. data analytical technique used is descriptive statistic, classic assumption test and hypothesis testing in the form of SmartPLS analysis. The test results show that the profitability, liquidity, and leverage variables affect the financial distress but growth didn’t affect. Company size can mediate the relation for variable profitability, leverage liquidity to financial distress.